2020
DOI: 10.1002/mp.14253
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of proton FLASH irradiation using a synchrocyclotron for preclinical studies

Abstract: It has been recently shown that radiotherapy at ultrahigh dose rates (>40 Gy/s, FLASH) has a potential advantage in sparing healthy organs compared to that at conventional dose rates. The purpose of this work is to show the feasibility of proton FLASH irradiation using a gantry-mounted synchrocyclotron as a first step toward implementing an experimental setup for preclinical studies. Methods: A clinical Mevion HYPERSCAN â synchrocyclotron was modified to deliver ultrahigh dose rates. Pulse widths of protons wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(107 citation statements)
references
References 33 publications
1
92
0
Order By: Relevance
“…Recent preclinical studies have suggested that ultra‐high‐dose‐rate (UHDR) “FLASH” irradiation may be superior to conventional radiation delivery in terms of sparing normal tissues 1–7 . In one of those studies, the incidence of lung fibrosis in mice exposed to 4.5 MeV electron beams at UHDR (40 Gy/s or higher) was lower at total doses higher than those used for irradiation at conventional dose rates (CDR).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent preclinical studies have suggested that ultra‐high‐dose‐rate (UHDR) “FLASH” irradiation may be superior to conventional radiation delivery in terms of sparing normal tissues 1–7 . In one of those studies, the incidence of lung fibrosis in mice exposed to 4.5 MeV electron beams at UHDR (40 Gy/s or higher) was lower at total doses higher than those used for irradiation at conventional dose rates (CDR).…”
Section: Introductionmentioning
confidence: 99%
“…Recent preclinical studies have suggested that ultra-highdose-rate (UHDR) "FLASH" irradiation may be superior to conventional radiation delivery in terms of sparing normal tissues. [1][2][3][4][5][6][7] In one of those studies, the incidence of lung fibrosis in mice exposed to 4.5 MeV electron beams at UHDR (40 Gy/s or higher) was lower at total doses higher than those used for irradiation at conventional dose rates (CDR). For example, irradiating mouse lungs to 17 Gy via CDR elicited fibrogenesis at 24 weeks after exposure, in contrast, at FLASH dose rates, only rare fibrotic patches were observed after exposure to 30 Gy.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the beam structure might be very important in realizing a good correction strategy for recombination effects in a proton facility. The challenge in obtaining a high-precision dose monitoring with ionization chambers was highlighted by Darafsheh et al [21]. In this study, the authors could measure more than 200 Gy/s dose-rate beams produced by a clinical synchro-cyclotron with a commercially available plane-parallel ionization chamber; however, the measured value was about 5% off the expectation, an uncertainty which might be due to several reasons.…”
Section: Control and Monitoringmentioning
confidence: 89%
“…This means that the beam consists of short pulses (order of 1 µs) repeated every 1-3 ms. As such, the use of synchrocyclotrons for FLASH irradiation seems to be challenging and might require some adaptations. For instance, a clinical Mevion HYPERSCAN ® (Mevion Medical Systems, Littleton, MA, USA ) system was modified to deliver ultra-high dose rates for FLASH experiments [21]. One of the key changes was an increased pulse width to 20 µs.…”
Section: Beam Structurementioning
confidence: 99%
“…5 The first application to a human was conducted on a skin tumor using a 5.6 MV electron linac 6 and experiments with protons on cells and mice, among other small animals, have been conducted or are under preparation. [7][8][9][10][11] After the HZB cyclotron was proven able to deliver FLASH proton radiation, 12 a dedicated nozzle was designed to enable Charit e to repeat its mice irradiation program under FLASH conditions. Besides the dose rate and the irradiation time, which were now aimed at 75 Gy(RBE)/s (RBE = 1.1) and 200 ms accordingly, the other specifications remained unchanged: 15 Gy(RBE) total dose with an error smaller than AE5%, 5 mm water-equivalent range with a spread-out Bragg peak (SOBP) and a distal fall-off (90%-10%) <1 mm, planning target volume (PTV) of 6 mm diameter with <10% uniformity, <5% symmetry, and <3 mm penumbra (90%-10%).…”
Section: Introductionmentioning
confidence: 99%